Detection of acoustic emission from nanofiber nonwovens under tensile strain – An ultrasonic test setup for critical medical device components. (April 2023) - Götz, Andreas; Senz, Volkmar; Schmidt, Wolfram; Koper, Daniela; Grabow, Niels; Illner, Sabine
Abstract: In the biomedical field, nanofiber materials are gaining increasing application. For material characterization of nanofiber fabrics, tensile testing and scanning electron microscopy (SEM) are established standards. However, tensile tests provide information about the entire sample without information about single fibers. Conversely, SEM images examine individual fibers, but cover only a small section near the surface of the sample. To gain information on failure at the fiber level under tensile stress, recording of acoustic emission (AE) is a promising method, but challenging due to weak signal intensity. Using AE recording, beneficial findings can be obtained even on "invisible" material failure without affecting tensile tests. In this work, a technology for recording weak ultrasonic AE of tearing nanofiber nonwovens is presented, which uses a highly sensitive sensor. Functional proof of the method using biodegradable PLLA nonwoven fabrics is provided. The potential benefit is demonstrated by unmasking significant AE intensity in an almost imperceptible bend in the stress-strain curve of a nonwoven fabric. AE recording has not yet been performed on standard tensile tests of unembedded nanofiber material intended for safety-related medical applications. The technology has the potential to enrich the spectrum of testing methods, even those not confined to medical field. Graphical abstract: Image 1 Highlights: Detection of weak ultrasonic AE signals during fracture of nanofiber fabrics. Advanced insights in failure process, identifying hidden (invisible) material defects. Contactless, cost-effective and easy to integrate into mechanical tests. Benefits for quality assurance, possible improvements for biomaterials and medical treatment.